Current Issue: Smoking Cessation, The Patient, The Physician and the Policy Makers - Ajayi, Tokunbo; Okudo, Jerome C (International Journal of Medical and Health Sciences Research, 2016)
Tobacco smoking continues to be a bane in the US. Nearly 540, 000 people die annually because of cigarette smoking. These deaths are preventable. Smoking is implicated in lung cancer and many other medical conditions. Billions of dollars have been spent on health issues related to smoking. Lung cancer affects men and women. Nicotine addiction is the culprit in continued smoking and understanding its role is important in promoting smoking cessation. Smoking cessation is important and scientific evidence and approaches exist in the literature. We have explored traditional, non-traditional and novel modalities for smoking cessation and the need for physicians to be actively involved in recommending smoking cessation. We have also discussed special populations that have special requirements for smoking cessation.